2016
DOI: 10.18383/j.tom.2016.00172
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Susceptibility Contrast-MRI Quantification Software Tool: Development and Evaluation

Abstract: Relative cerebral blood volume (rCBV) is a magnetic resonance imaging biomarker that is used to differentiate progression from pseudoprogression in patients with glioblastoma multiforme, the most common primary brain tumor. However, calculated rCBV depends considerably on the software used. Automating all steps required for rCBV calculation is important, as user interaction can lead to increased variability and possible inaccuracies in clinical decision-making. Here, we present an automated tool for computing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These were then registered to the T1 weighted post-contrast images using ANTs [19]. We calculated the mean, median, 95th and 20th percentile values for ADC pixels corresponding to the CEROI, referred to as ADCmn, ADCmed, ADC95, ADC20 [20].…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…These were then registered to the T1 weighted post-contrast images using ANTs [19]. We calculated the mean, median, 95th and 20th percentile values for ADC pixels corresponding to the CEROI, referred to as ADCmn, ADCmed, ADC95, ADC20 [20].…”
Section: Image Processingmentioning
confidence: 99%
“…We computed relative cerebral blood volume (rCBV), K2, and Peak Signal Recovery (PSR) images from the dynamic susceptibility contrast (DSC) source images [20]. The dynamic susceptibility contrast (DSC) images were acquired with a 128 × 128 matrix to cover the brain, and with 10-12 slices that were 5 mm thick with 1 mm gap, to cover the tumor.…”
Section: Image Processingmentioning
confidence: 99%
“…For example, the accuracy of rCBV depends on acquisition parameters such as TE and flip angle 14 . The calculation of leakage correction is software dependent 24 , 25 , and the percentage signal recovery is also influenced by contrast agent preload and pulse sequence parameters 8 . Indeed, when we compared the average rCBV values, the rCBVs of glioblastoma were 5.52 ± 2.33 (mean ± standard deviation) vs. 7.34 ± 1.51 in the internal and external validation sets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown interrater variability when ROIs are manually drawn. 16,24,25 In our study, the AUROC of rCBV for a manually drawn NAWM was 0.78, and is similar to ROC results published by Tietze et al, where their AUROC for rCBV was 0.78. 26 Here we demonstrate that using an automatically segmented ROI for rCBV increases the AUROC to 0.86.…”
Section: Discussionmentioning
confidence: 99%